Anticholinergics: A potential option for preventing posttraumatic epilepsy - Sanabria, Viviam; Romariz, Simone; Braga, Matheus; Foresti, Maira Licia; Naffah-Mazzacoratti, Maria da Graça; Mello, Luiz Eugênio; Longo, Beatriz M. (Frontiers in Neuroscience, 2023)
Interest in the use of anticholinergics to prevent the development of epilepsy after traumatic brain injury (TBI) has grown since recent basic studies have shown their effectiveness in modifying the epileptogenic process. These studies demonstrated that treatment with anticholinergics, in the acute phase after brain injury, decreases seizure frequency, and severity, and the number of spontaneous recurrent seizures (SRS). Therefore, anticholinergics may reduce the risk of developing posttraumatic epilepsy (PTE). In this brief review, we summarize the role of the cholinergic system in epilepsy and the key findings from using anticholinergic drugs to prevent PTE in animal models and new clinical trial protocols. Furthermore, we discuss why treatment with anticholinergics is more likely to prevent PTE than treatment for other epilepsies.